PROFIL KEMAMPUAN LITERASI SAINS CALON GURU SD: ANALISIS PADA ASPEK KOMPETENSI - Mulyani, Hanifah; Rizki hadiwijaya Zulkarnaen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to describe the profile of scientific literacy of elementary school teacher candidates, especially in aspect of their competencies. Based on OECD, this aspect focusing on three indicators, such as explaining phenomena scientifically; evaluating and designing scientific enquiry; and interpreting data and evidence scientifically. The method used in this research is quantitative descriptive, involving 65 elementary school teacher candidates as the research subject. As the research instrument, ten close-ended questions were given to the subject and all data were processed through some techniques, starting from data collection, data cleaning, exploratory data analysis, data organization, statistical analysis, to result interpretation. Based on the result of this research, the scientific literacy’ average score on competency aspect of elementary school teacher candidate was around 51 and categorized as medium. The highest average score was 90 while the lowest was 7. The various number certainly was caused by several factors, such as different educational background, passion and curiosity, learning style and method, and etc. These result indicated that there must be some strategies to be conducted in science learning process to facilitate those teacher candidates in increasing their scientific literacy, especially in competency aspect.